Preparation of Peptide o-Aminoanilides Using a Modified Dawson's Linker for Microwave-Assisted Peptide Synthesis - Tsuda, Shugo; Uemura, Tsuyoshi; Mochizuki, Masayoshi; Nishio, Hideki; Yoshiya, Taku (Synlett, 2017)
Based on the structure of Dawson’s 3,4-diaminobenzoic acid (Dbz) linker designed for Fmoc solid-phase peptide-thioester synthesis, the 4-amino-3-nitrobenzoic acid [Dbz(NO2)] linker was developed for microwave-assisted synthesis. The Dbz(NO2) linker can be readily converted into the Dbz linker by on-resin reduction with SnCl2 after construction of the protected peptide resin. Although epimerization of C-terminal amino acid restricts the use of Dbz(NO2) linker to the synthesis of peptide-Gly-thioester, use of this linker can prevent side reactions that arise when Dbz or Dbz(Aloc) linkers are used in the microwave-assisted synthesis of Gly-rich peptides.
Keywords: Dawson’s linker; microwave; NCL; peptide synthesis; thioester